CRISPR/Cas9 based mlo-mediated resistance against Podosphaera xanthii in cucumber (Cucumis sativus L.) - Tek, Mumin Ibrahim; Calis, Ozer; Fidan, Hakan; Shah, Mehraj D.; Celik, Sefanur; Wani, Shabir Hussain (Frontiers in Plant Science, 2022)
Powdery mildews (PM) are common and severe pathogen groups that threaten plants, and PM resistance is complex and polygenic in cucumbers. Previously mlo-based resistance was reported in various plants, including cucumber, with generated loss-of CsaMLO function mutants. However, mlo-based resistance in cucumber is also complex and involves additional mechanisms such as hypersensitive response (HR) and papillae formation. For this reason, we focused on determining the mlo-based powdery mildew resistance mechanism in cucumber. CRISPR/Cas9 was used in the present study to generate loss-of-function mutants for CsaMLO1, CsaMLO8, and CsaMLO11 of PM susceptible ADR27 cucumber inbred lines and CsaMLO mutants were obtained and validated. Trypan Blue and DAB staining were performed to detect Podosphaera xanthii germination/penetration rates and accumulation of Reactive Oxygen Species (ROS). Our results indicate that PM-susceptibility associated CsaMLOs in cucumber are negative regulators in different defense mechanisms against powdery mildew at early and late stages of infection. Further, the experiment results indicated that CsaMLO8 mutation-based resistance was associated with the pre-invasive response, while CsaMLO1 and CsaMLO11 could be negative regulators in the post-invasive defense response in cucumber against P. xanthii. Although the loss-of CsaMLO8 function confers the highest penetration resistance, CsaMLO1 and CsaMLO11 double mutations could be potential candidates for HR-based resistance against PM pathogen in cucumber. These results highlighted the crucial role of CRISPR/Cas9 to develop PM resistant cucumber cultivars, possessing strong pre-invasive defense with CsaMLO8 or post-invasive with CsaMLO1/CsaMLO11 mutations.